The Identity of Psychiatry and the Challenge of Mad Activism: Rethinking the Clinical Encounter. Issue 6 (3rd July 2020) - Rashed, Mohammed Abouelleil
Abstract: Central to the identity of modern medical specialities, including psychiatry, is the notion of hypostatic abstraction: doctors treat conditions or disorders, which are conceived of as "things" that people "have." Mad activism rejects this notion and hence challenges psychiatry's identity as a medical specialty. This article elaborates the challenge of Mad activism and develops the hypostatic abstraction as applied to medicine. For psychiatry to maintain its identity as a medical speciality while accommodating the challenge of Mad activism, it must develop an additional conception of the clinical encounter. Toward elaborating this conception, this article raises two basic framing questions: For what kind of understanding of the situation should the clinical encounter aim? What is the therapeutic aim of the encounter as a whole? It proposes that the concepts of "secondary insight" (as the aim of understanding) and of "identity-making" (as a therapeutic aim) can allow the clinical encounter to proceed in a way that accommodates the challenge of Mad activism.